2013
DOI: 10.1038/leu.2013.119
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and prognosis in primary myelofibrosis

Abstract: Patient outcome in primary myelofibrosis (PMF) is significantly influenced by karyotype. We studied 879 PMF patients to determine the individual and combinatorial prognostic relevance of somatic mutations. Analysis was performed in 483 European patients and the seminal observations were validated in 396 Mayo Clinic patients. Samples from the European cohort, collected at time of diagnosis, were analyzed for mutations in ASXL1, SRSF2, EZH2, TET2, DNMT3A, CBL, IDH1, IDH2, MPL and JAK2. Of these, ASXL1, SRSF2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
663
6
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 672 publications
(743 citation statements)
references
References 48 publications
31
663
6
20
Order By: Relevance
“…In multivariable analysis that included all prognostically relevant mutations, 3 absence of CALR (hazard ratio (HR), 2.6; 95% confidence interval (CI), 1.8-3.9), presence of ASXL1 (HR, 2.0; 95% CI, 1.5-2.7) and presence of SRSF2 (HR, 1.7; 95% CI, 1.1-2.8) mutations were significantly associated with shortened survival; EZH2 (P ¼ 0.07) or IDH (P ¼ 0.48) mutations were not significant. Absence of CALR (HR, 2.3; 95% CI, 1.5-3.5) and presence of ASXL1 (HR, 1.5; 95% CI, 1.1-2.1) mutations remained significant when DIPSS-plus risk stratification was added into the multivariable model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In multivariable analysis that included all prognostically relevant mutations, 3 absence of CALR (hazard ratio (HR), 2.6; 95% confidence interval (CI), 1.8-3.9), presence of ASXL1 (HR, 2.0; 95% CI, 1.5-2.7) and presence of SRSF2 (HR, 1.7; 95% CI, 1.1-2.8) mutations were significantly associated with shortened survival; EZH2 (P ¼ 0.07) or IDH (P ¼ 0.48) mutations were not significant. Absence of CALR (HR, 2.3; 95% CI, 1.5-3.5) and presence of ASXL1 (HR, 1.5; 95% CI, 1.1-2.1) mutations remained significant when DIPSS-plus risk stratification was added into the multivariable model.…”
Section: Resultsmentioning
confidence: 99%
“…7 Before the discovery of CALR mutations in ET and PMF, we had identified mutant ASXL1 as dynamic international prognostic scoring system (DIPSS)-plus 10 and IPSS 11 independent risk factor for survival in PMF. 3 More recently, we discovered the prognostic synergism between CALR and ASXL1 mutations in PMF and highlighted the inferior survival associated with 'CALR À ASXL1 þ ' mutational status. 7 The main objective of the current study was to further explore the prognostic interaction between CALR and ASXL1 mutations in PMF with the intent to derive (using a patient cohort from the Mayo Clinic, USA) and validate (using a patient cohort from the University of Florence, Italy) a molecular prognostic model, in the context both DIPSS-plus and IPSS.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Specific genes affected in this regard include those relevant to epigenetic (e.g., ASXL1, TET2, EZH2, IDH1, IDH2, DNMT3A), RNA splicing (e.g., SRSF2, U2AF1, SF3B1) or transcriptional (TP53, IKZF1, NF-E2, CUX1) regulation. Mutations other than JAK2, CALR or MPL, which have been shown to have prognostic relevance in PMF, include ASXL1, SRSF2, EZH2, IDH1/2, and U2AF1 [51,52]. In addition, TP53, IDH2, SRSF2, and SH2B3 mutations have been reported to be over-represented in blastphase MPN, suggesting their relevance in disease progression [48,50,53].…”
Section: Pathogenetic Contribution Of Mutations In Myeloproliferativementioning
confidence: 99%
“…More recently, a number of DIPSS-plus-independent risk factors in PMF were identified and they include driver mutations other than type 1 or type 1-like CALR variants [44], monosomal karyotype [74], nullizygosity for JAK2 46/1 haplotype [75], low JAK2V617F allele burden [76,77], presence or number [78] of IDH1/2 [51], EZH2 [51], SRSF2 [51], or ASXL1 mutations [51], and increased serum IL-8 [79], IL-2R [79] or serum free light chain levels [80]. In a recent international study of 570 patients with PMF [81], the authors reported the longest …”
Section: Advances In Prognosticationmentioning
confidence: 99%